Tsounkranaglenea hefferni gen. et sp. nov. from Sabah, Malaysia (Coleoptera, Cerambycidae, Lamiinae: Saperdini) - Lin, Mei-Ying; Ge, Si-Qin (Zootaxa, 2021)
A new saperdine species belonging to a new genus, Tsounkranaglenea hefferni gen. et sp. nov., is described from Sabah, Malaysia. The new genus differs from other genera of the tribe Saperdini by the special male sternite VII modified into a rake-shape, with the apex of the ventral plate of the median lobe unusually emarginated.